An Analysis of Different Techniques Used to Seal Post-Extractive Sites-A Preliminary Report - Paolo Pesce; Eitan Mijiritsky; Luigi Canullo; Maria Menini; Vito Carlo Alberto Caponio; Andrea Grassi; Luca Gobbato; Domenico Baldi (MDPI AG, 2022)
Background: Bone grafting in post-extractive site improves tissue regeneration. Soft tissue sealing of the grafted post-extractive alveolus is supposed to limit microbiological contamination from the oral cavity and to stabilize the coagulum. Several techniques are presented in the literature to reach this goal using different heterologous matrices or autogenous grafts. In addition, recently, a technique based on the use of granulation tissue in the post-extractive alveolus has been proposed. Aim: To compare the effect of different graft sealing approaches in post-extractive sites by qualitatively evaluating their healing process. Materials and Methods: This retrospective investigation included 30 patients requiring post-extractive site regeneration in the aesthetic area. Post-extractive sites were regenerated using a bovine bone matrix and patients were divided into three groups (10 patients in each group) according to the material used to seal the alveolar socket. In the UD group, the granulation tissue was used to seal the defect; in the PC group, epithelial-connective soft tissue graft was used, and in the COLL group, a collagen-based membrane was employed. Images of the post-extractive sites at different follow-up periods (2 and 12 weeks) were taken and the healing process was blindly evaluated by two independent practitioners. The Healing Index (HI) by Landry, Turnbull and Howley was used to assess the quality of the healing process. The combination of presence/absence of five clinical criteria defines an HI ranging from 1 (very poor) to 5 (excellent). Patients' clinical-pathological variables were recorded. One-way ANOVA was used to explore the dependence of HI on the different socket preservation protocols. Results: Based on clinical-pathological characteristics of the included patients, there were no statistically significant differences among the different sealing techniques. At the 2-week follow-up appointment, HI did not differ among the socket preservation protocols evaluated. Moreover, smoking status and reason for extraction did not influence the HI among the three groups (two-way ANOVA p-value = 0.686, p-value = 0.248 respectively). At the 2-week follow-up appointment, HI was significantly different among the socket preservation protocols investigated. Specifically, the group undergoing collagen-based socket preservation procedure reported the highest HI, compared to the other two techniques (COLL mean 4.60 ± 0.5; PC mean 3.5 ± 1.2; UD mean 3.4 ± 0.5, one-way ANOVA p-value 0.006). Conclusions: The use of collagen porcine membranes may represent a suitable option to improve the patient healing process in grafted post-extractive sites together with reducing the surgical intervention time compared to alternative sealing techniques.